1996
DOI: 10.2165/00002018-199614060-00006
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Pancreatitis

Abstract: Few data exist about the incidence of drug-induced pancreatitis in the general population. 20 cases of drug-related pancreatitis were reported in Switzerland over a period of 12 years. The proportion of cases of pancreatitis caused by drugs is estimated to be around 2% in the general population, with much higher proportions in specific subpopulations, such as children and patients who are HIV positive. The literature about drug-induced pancreatitis consists mainly of anecdotal case reports. Clear evidence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 250 publications
2
78
0
1
Order By: Relevance
“…The development of pancreatitis has been related to more than 55 different drugs. [9][10][11][12] VPA definitely has been associated with pancreatitis, based upon a series of well documented cases. 1 VPA-induced pancreatitis occurs most frequently under the age of 20 and nearly half of the cases present within the first three months after initiation of treatment, though pancreatitis can also develop after years of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The development of pancreatitis has been related to more than 55 different drugs. [9][10][11][12] VPA definitely has been associated with pancreatitis, based upon a series of well documented cases. 1 VPA-induced pancreatitis occurs most frequently under the age of 20 and nearly half of the cases present within the first three months after initiation of treatment, though pancreatitis can also develop after years of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The responsible drugs have been categorized based on definite, probable, and possible causality. A careful review of all drugs received by our patient during her hospitalization revealed three incriminating medications: enalapril, nonsteroidal anti-inflammatory drugs (NSAIDs), and furosemide, the former two in the probable and the latter in the possible causality category [16]. However, unlike all reported cases of enalapril-related pancreatitis, our patient had been continually on this medication for several years [16].…”
Section: Discussionmentioning
confidence: 70%
“…Drugs have long been regarded as an important cause of pancre- atitis. However, this traditional view has been questioned [12] and the true incidence of drug induced pancreatitis is estimated to be between 1 and 2% [7,16]. The responsible drugs have been categorized based on definite, probable, and possible causality.…”
Section: Discussionmentioning
confidence: 99%
“…In 20% of cases, the cause remains unidentified [8]. Drugs are implicated in only 2-5% of cases, either by a hypersensitivity reaction or the generation of a toxic metabolite [14], although it is frequently difficult to prove causality [9].…”
Section: Discussion and Conclusion:-mentioning
confidence: 99%